Pengembangan Model Permainan Kereta Air untuk Pengenalan Air Bagi Pemula Usia 6-8 Tahun Di Klub Renang Amarta Aquatic Kota Malang - Mustaqim; Roesdiyanto (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2018)
The development of a water game model is an exercise for beginners who have never swam before. This development research aims to eliminate the fear of water and introduce the nature of water such as cold, wet and water resistance for beginners aged 6-8 years. This research and development use Borg and Gall model consisting of seven stages: requirement analysis, initial product design, expert evaluation, small group trial, product revision, and large group trial. The subjects of small group trials are 10 swimmers while the subjects of large group trials are 30 class swimming pool toddler swimming pool Amarta Aquatic Malang. Aspects that are measured on small group trials and large groups are attractiveness, ease and pleasure. The average result of the percentage of small group trials is 85% (very good) while large group trials are 85% (very good). The conclusion based on the research results is the development of water train model for water introduction for beginners aged 6-8 years in the pool club Amarta Aquatic Malang is very valid so it is feasible to use in the introduction of water.